Plaisirs croisés: gukuna-kunyaza. Missions, corps et sexualités dans le Rwanda contemporain - Michela Fusaschi (Genre, Sexualité et Société, 2012)
Based on ethnographic research in post-genocide Rwanda, this article analyzes how femininity is embodied through a ritual practice called gukuna, which consists of the elongation of the labia minora through a reciprocal massage between young women. This social construction of the female body, in addition to kunyaza, a traditional male sexual technique, is expected to facilitate pleasure during sexual intercourse. Through an analysis of colonial period texts as well as recent interviews, this article shows how this ritual, has persisted in the country despite its condemnation by the Catholic Church since the colonial time, and explores how it is being reinterpreted by women.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afro-féminisme; approches et analyses; corps; cours; discipline; féminisme africain; gukuna; premier cycle; périodes historiques; rituel; rwanda; régions géographiques; science politique; science politique et droit; sex2283; sexualité; thématiques